Meningkatkan Hasil Belajar Senam Lantai dengan Menggunakan Metode Demonstrasi Siswa Kelas III SD Negeri 2 Cakranegara - Asriana, Akhmad (Lembaga Yasin AlSys, 2022)
The purpose of this study was to improve learning outcomes of floor gymnastics by using the demonstration method for third grade students of SD Negeri 2 Cakranegara in the 2021/2022 academic year. Sources of data in this study were the third grade students of SD Negeri 2 Cakranegara totaling 27 students. Data collection techniques with assessment tests and observations. The data analysis technique used in this research is descriptive qualitative and the percentage is based on data from the results of tests conducted by students. Based on the results of the study, it was concluded that the application of the demonstration method can be considered for PJOK teachers to be applied in learning floor gymnastics. The results of this study are expected to be a concern for schools to provide encouragement to teachers to apply learning methods and use appropriate media as an effort to achieve quality learning to achieve the goals of physical education, sports, and health outlined in the curriculum. For further researchers, the results of this study can be used as input and insight into the use of games and image media in improving floor gymnastics learning.